PS1 - 163 Engaging in Difficult Discussions with Neuro-Oncology Patients: A Case Conference Based Quality Improvement Initiative. (18th October 2016) - Mueller, C.; Bilodeau, D.B.; Chakraborty, A.C.; Ellis, J.E.; Gibson, L.G.; Isenberg-Grzeda, E.I.; Moroney, C.M.; Myers, J.M.; Scalco, A.S.; Speke, A.S.
Abstract : Due to the non-curative nature of high grade brain tumours "difficult discussions" about goals of care, advance care planning, palliative care, and end of life are inherent to the practice of the neuro-oncology team. Clinician and patient barriers are common and may include anxiety about destroying hope, lack of readiness to discuss end of life topics, difficulty managing emotional responses, and concerns over competency in facilitating difficult discussions. Nonetheless, clinician comfort and skill in facilitating these discussions is critical and can impact patient perception of illness, coping response, and ability to make decisions about care. Methods At our regional cancer centre, a novel quality improvement initiative was designed to bring monthly case presentation of "difficult discussions" into a pre-existing weekly multi-disciplinary case conference (MCC). We will describe the rationale and developmental processes behind this initiative. Roughly 15 neuro-oncology clinicians attended each case conference, with guest attendance from palliative care and psychosocial oncology. Clinician groups represented included physicians (77%), nurses (8%), nurse practitioners (10 %), and occupational therapists (5%). Baseline and monthly surveys were administered to determine clinicians' self- rated practices, skills, and attitudes towards "difficult discussions". Results Early findings indicate that the initiative has been well-received. Physicians indicated highest levels of agreement with the statement "I feel that having difficult discussions is part of my responsibility". Non physician groups indicated the greatest agreement that the intervention is beneficial to their practice. Discussion: Our challenges and successes may help guide others to incorporate a similar initiative at disease-site meetings.